Microstructural and UCS behavior of clay soils stabilized with hybrid nano-enhanced additives - Dogan, Nagihan; Firat, Muge Elif (De Gruyter Poland Sp Z O O, 2026)
In this study, both individual and hybrid effects of industrial wastes (silica fume, fly ash), fibers (glass and basalt) and nanoparticles (nano SiO2, nanoclay) mixed with clay at different ratios were investigated in detail at macro and micro levels at different water contents and curing times. The efficiency of stabilization in clay soils was determined using Gray Correlation Analysis (GCA). A predictive model for the stress-strain relationship of stabilized soils with hybrid material was proposed. Results showed negligible changes in dry density and optimum moisture content with silica fume and fly ash, while nano SiO2 and nanoclay induced significant variations. The unconfined compressive strength (UCS) tests showed a significant increase in soil strength with the addition of nanomaterials, especially after long curing times. The presence of nano SiO2 and nanoclay in the composite specimens increased the UCS by 87.15 % and 63.83 % before curing, respectively, while it increased to 317.50 % and 219.74 % after the maximum curing time. GCA identified curing time as the most influential factor, followed by silica fume, glass fiber, and nanoclay, due to progressive bonding development. Nanoclay demonstrated superior UCS enhancement compared to nano SiO2, underscoring its effectiveness in soil stabilization. The study contributes to the literature to realize the full benefits of these additives to improve soil stability and the UCS performance, and to address waste recycling, increase the strength of subgrade soils under different environmental conditions, and reduce the costs associated with the use of waste.
Keywords: clay soil; UCS; industrial wastes; fibers; nanoparticles; optimization